2021
DOI: 10.3390/ijerph19010003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tug of War Competition: A Narrative Complete Review

Abstract: Tug-of-war (TOW) is an internationally played activity including professional and amateur athletes, defined as early as 4000 years ago (as a rope-less version) in the artwork on Egyptian tomb engravings, and is played as per the rules laid out by TWIF, which has 73 member countries and administrative headquarters in the USA. Typically, two teams of “pullers” participate and apply enormous contra directional forces on the pulling rope. Originally, two types of competition are used: knockout and points. This nar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…It is important to take into account that in order to improve the grip on the ground and the traction that the pullers make, in the outdoor modality, all perform a rotation of the lower part of the trunk towards the right side. This rotation allows them to place their feet sideways on the ground, and to be able to pull with a greater surface area on the mud (Cayero et al, 2022). Regarding the differences registered in the lower body, many of them are conditioned to a large extent by the material used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation

Diferencias cinemáticas en el Tug of War indoor y outdoor: Estudio de caso

Arkaitz Castañeda-Babarro,
Julio Calleja-González,
Asier Zubillaga
et al. 2023
ebm.jss
“…It is important to take into account that in order to improve the grip on the ground and the traction that the pullers make, in the outdoor modality, all perform a rotation of the lower part of the trunk towards the right side. This rotation allows them to place their feet sideways on the ground, and to be able to pull with a greater surface area on the mud (Cayero et al, 2022). Regarding the differences registered in the lower body, many of them are conditioned to a large extent by the material used.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is a sport with a long history and practiced all over the World, (being of the oldest), little research has been published about performance parameters (Cayero et al, 2022).…”
Section: Introductionmentioning
confidence: 99%

Diferencias cinemáticas en el Tug of War indoor y outdoor: Estudio de caso

Arkaitz Castañeda-Babarro,
Julio Calleja-González,
Asier Zubillaga
et al. 2023
ebm.jss
“…Tug of war (also known as tug o' war, tug war, rope war, rope pulling, or tugging war) refers to "an athletic contest between two teams who haul at the opposite ends of a rope, each trying to drag the other over a line marked between them" [1]. Tug of war has a rich history and unclear origins and is arguably one of the oldest known games in humanity, played for ritual, political, military, commemorative, sportive, or recreational (1) purposes in various cultures [2][3][4]. Its most ancient representations can be traced back to as early as the Bronze Age 1 [5], and historical and mythological variants can be found galore, for example, in ancient Greece [6], Cambodia, 2 China [4], India, 3 Afghanistan, Japan, Korea, South America, Europe, and Togo; as well as in Inuit traditions [7] or Scandinavian legends [8].…”
Section: Introductionmentioning
confidence: 99%
“…Tug of war has a rich history and unclear origins and is arguably one of the oldest known games in humanity, played for ritual, political, military, commemorative, sportive, or recreational (1) purposes in various cultures [2][3][4]. Its most ancient representations can be traced back to as early as the Bronze Age 1 [5], and historical and mythological variants can be found galore, for example, in ancient Greece [6], Cambodia, 2 China [4], India, 3 Afghanistan, Japan, Korea, South America, Europe, and Togo; as well as in Inuit traditions [7] or Scandinavian legends [8]. Rope pulling is now a codified sport [9], played in all countries in the world by amateur and professional athletes.…”
Section: Introductionmentioning
confidence: 99%
“…This would help in the preliminary diagnosis for decision making regarding program design, establishing training objectives, applying specific tests and any other evaluation in sports planning [10]. However, to the best of the authors' knowledge, and based on a recent work published by our research group [11], in which the state of the art has been compiled, we have identified that no previous articles have described the duration of the indoor pulls, and even fewer data have been obtained during a follow-up on the best TOW athletes in the world during the highest level of competition. Therefore, the main aim of this article was to analyze the durations of the matches, differentiating between the first (T1) and second pull (T2) of each match.…”
Section: Introductionmentioning
confidence: 99%